BS P02 Sleeve gastrectomy and gastric bypass day surgery: outcomes and experience from a single centre. (7th December 2022) - Katz-Summercorn, Annalise; Shah, Runil; Arhi, Chanpreet; Musendeki, Debbie; Fitt, Irene; McGrandles, Rosie; Zalin, Anjali; Rashid, Farhan; Adil, Md Tanveer; Jain, Vigyan; Mamidanna, Ravikrishna; Jambulingam, Periyathambi; et al.
Abstract: Background: Internationally, day case Bariatric surgery has been shown to be safe, feasible and economically beneficial. However, it has not been widely adopted in the UK. It requires careful patient selection and a mature enhanced recovery programme. We report on the outcomes and lessons learned during our 2.5-year experience of day case laparoscopic sleeve gastrectomies (LSG) and Roux-en-y gastric bypass (RYGB) operations. Methods: A retrospective analysis was performed of all patients who were selected as candidates for day case Bariatric surgery in a single-centre since October 2019. Patients were considered eligible if they had a BMI <60, lived within 30 minutes of the hospital, were having primary surgery with no additional procedure and were not on CPAP. All patients received a nurse-led telephone assessment on day 1. Rates of successful discharge, patient demographics, readmission and outcomes were analysed. Results: Thirty-nine patients were identified as suitable candidates for day case operations: 24 (62%) RYGB, 15 (38%) LSG. The mean BMI was 46.5; 85% female. The main reason for not being considered was the patient living >30 minutes away. Overall, 18 (13 RYGB, 5 LSG; 46.2%) were successfully discharged on the day of surgery. Fifteen (38.5%) were discharged on the first post-operative day and 6 (15.4%) stayed two or more days. The commonest reasons for failed discharge were nausea/vomiting 6 (15.4%) and logistical issues e.g. operation in the afternoon 6 (15.4%). There was one readmission within 30 days (sealed leak from the gastro-jejunal anastomosis) but no returns to theatre. Conclusions: We have successfully performed day case Bariatric surgery in our centre. However, it is a logistical challenge and to date has only been carried out successfully on a small number of patients. The main challenge being the vast catchment area for our tertiary centre. Further work is needed to better define the parameters for patient eligibility in order to safely offer this to more patients.